Do ocaso do curso normal à alvorada da educação profissional e tecnológica: políticas educacionais e experiências de Santa Maria e Pelotas/RS - Lampe, Leandro (2021)
The Normal Course, which historically prepares professionals for Education, has, throughout its trajectory, suffered impacts from educational policies and reforms, impacts that provoke different experiences in the Courses. In this sense, this dissertation, which has as its object of study the Normal Course and Professional and Technological Education, has as its problematization the question: what are the approaches and distances of the meanings of the Normal Course as EPT, from the policies and training experiences of teachers for the initial years in the Normal Schools of Santa Maria and Pelotas? To this end, the general objective was to analyze the meanings of approximations and distances from the Normal Course as EPT, from the policies and experiences of teacher training for the early years in the Normal Course schools of Santa Maria and Pelotas, and as specific objectives : I) Contextualize the policy of training teachers at secondary level and the policy of Vocational Education; II) Systematize the Normal Course in the National Catalog of Technical Courses in its four editions and in Professional Education in Brazil; III) Develop theoretical framework on the historicity of the Normal Course in public schools in Santa Maria and Pelotas and IV) Understand the training of teachers at high school, currently, in schools in Santa Maria and Pelotas. The production of data was through documentary and bibliographic research during the study, a questionnaire with the students of the Normal Course, two Focus Groups and a Interlocution Group carried out with the coordinators of the courses of both institutions. As a theoretical-methodological contribution, which also served as an analysis technique, we resorted to the Analysis of Movements of Meaning, which has been developed by the Kairós Group. The Kairós - Study and Research Group on Work, Education and Public Policies, which added to the TransformAção group - Study and Research Group on Public Policies and Pedagogical Work in Professional Education, constitute the scope in which the study was constituted. From the analysis, the senses of approximation were evidenced i) Training for work and ii) Work as an educational principle and the sense of detachment iii) Work for Education. With the results, it was possible to make some final notes, which indicate that the Course, despite being heading towards the end, continues to exist and resists the implementation of policies that do not contemplate it, and thus present themselves as a threat. The existence and resistance is only possible nowadays due to the pedagogical work developed by the subjects that make up the Courses.